The Fostering of Piano Beginners’ Improvisation Skills through Rhythmic Movement Exercises - Assavanop, Tarudee; Udtaisuk, Dneya (An Online Journal of Education, 2021)
The purpose of this research was to study the quality of piano beginners’ melodic and rhythmic improvisation skills through rhythmic movement exercises. The participants consisted of 3 piano beginners, who studied piano with the researcher. The research used the Single-Group Pretest-Posttest Design. The tools included rhythmic movement exercises, which were used as experimental tools, and the data collection tool was an improvisational skills’ evaluation form. The researcher analyzed the outcome using quantitative analysis and qualitative analysis. For instance, the quantitative analysis was performed by calculating the average scores of each student’s improvisation skill and comparing each student’s pre-test to post-test development. Moreover, the qualitative analysis was in the form of music notation with respect to the characteristics of each student’s improvisation skills. The results revealed that each participants’ individual improvisation skills improved differently. Specifically, it was found that students who had studied piano for 2 years were more able to improve their improvisation skills than students who had studied piano for no longer than 3 months.